Modulation Scheme Based on Precoder Matrix for MIMO Optical Wireless Communication Systems - Wu, Liang; Zhang, Zaichen; Liu, Huaping (IEEE communications letters, 2012)
A modulation scheme for multiple-input multiple-output (MIMO) optical wireless systems that employ intensity modulation (IM) is proposed. This scheme, called precoder matrix modulation (PMM), exploits the properties of MIMO optical wireless communications to translate the spatial dimension into the constellation parameters by using a 'precoder matrix'. The transmitted signals in PMM are guaranteed to be nonnegative, as required in IM optical wireless communications. Existing schemes such as pulse-amplitude modulation could be used in such systems, but the proposed scheme has a much better performance. The constellation size of PMM can be flexibly increased, mitigating the bandwidth shortage issue due to the limitation of light emitting diodes (the transmitters).